Monotone Methods for Markovian Equilibrium in Dynamic Economies - Manjira Datta; Leonard J. Mirman; Olivier F. Morand; Kevin L. Reffett (Tinbergen Institute, 2002)
In this paper, we provide an overview of an emerging class of monotone map methods in analyzing distorted equilibrium in dynamic economies. In particular, we focus on proving the existence and characterization of competitive equilibrium in non-optimal versions of the optimal growth models. We suggest two alternative methods: an Euler equation method for a smooth, strongly concave environment, and a value function method for a non-smooth supermodular environment. We are able to extend this analysis to study models that allow for unbounded growth or a labor-leisure choice.
Keywords: 330; Dynamisches Gleichgewicht; Optimales Wachstum; Gleichgewichtstheorie; Theorie